Association between height and hypertension among US adults: Analyses of National Health and Nutrition Examination Survey 2007–18 - Gupta, Rajat Das; Akonde, Maxwell; Sajal, Ibrahim Hossain; Al Kibria, Gulam Muhammed (BMC, 2022)
This article was published in the Clinical Hypertension by BMC [© The Author(s). 2021 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use] and the definite version is available at: https://doi.org/10.1186/s40885-021-00164-4 The Journal's website is at: https://clinicalhypertension.biomedcentral.com/articles/10.1186/s40885-021-00164-4